An improvement of time-reassigned synchrosqueezing transform algorithm and its application in mechanical fault diagnosis. (April 2020) - Cao, Hongrui; Wang, Xiangsheng; He, Dong; Chen, Xuefeng
Highlights: An improved fast calculation method for TSST is proposed. The proposed method still has a high concentration of the TF representation. The proposed method is verified with both simulations and experiments. Abstract: Time-reassigned synchrosqueezing transform (TSST) provides a high concentration of the time–frequency (TF) representation of impulsive-like signals. However, when TSST is used to process non-stationary real-world signals, it often faces a large number of data points which will cause huge computational overhead. To address this problem, an improved algorithm for TSST is proposed in this paper. The improved algorithm mainly includes the following ideas: increasing the window function shifting point number H and decreasing the point number Nf of Fourier transform combining fast matrix operation and time–frequency band selection and reassignment. Moreover, in order to ensure phase consistency in the time-reassigned operation, phase correction is carried out for the TF matrix. The proposed method is validated with numerical simulation and then applied in mechanical fault diagnosis. The results show that the method can greatly improve computational efficiency while ensuring a high concentration of the TF representation.